2019
DOI: 10.1016/j.gene.2019.144107
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Coronary Artery Disease methylome through targeted bisulfite sequencing

Abstract: Background: Gene environment interactions leading to epigenetic alterations play pivotal role in the pathogenesis of Coronary Artery Disease (CAD). Altered DNA methylation is one such epigenetic factor that could lead to altered disease etiology. In this study, we comprehensively identified methylation sites in several genes that have been previously associated with young CAD patients. Methods:The study population consisted of 42 healthy controls and 33 young CAD patients (age group < 50 years). We performed t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Of note, GALNT2 mRNA levels remain significantly associated with TG but no longer with HDL-C in conditional analyses including both lipid fractions, thus suggesting the association with HDL-C is mainly mediated by the very much expected strong and inverse correlation between HDL-C and TG levels [88]. Finally, the GALNT2 promoter is hyper-methylated, a proxy of gene down-regulation, in patients with CAD and low HDL-C levels [19,89].…”
Section: Galnt2 and Atherogenic Dyslipidemiamentioning
confidence: 97%
“…Of note, GALNT2 mRNA levels remain significantly associated with TG but no longer with HDL-C in conditional analyses including both lipid fractions, thus suggesting the association with HDL-C is mainly mediated by the very much expected strong and inverse correlation between HDL-C and TG levels [88]. Finally, the GALNT2 promoter is hyper-methylated, a proxy of gene down-regulation, in patients with CAD and low HDL-C levels [19,89].…”
Section: Galnt2 and Atherogenic Dyslipidemiamentioning
confidence: 97%
“…Ghose, S. et al . reported that LDLR gene undergoes hypomethylation and induces an increased expression which subsequently decreases the LDL levels and reduces the risk of CAD 94 . In the present study, we have observed that 31% of CpG SNVs abolished the CGI existence and ~ 44% decreased the size of CGI.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Finally, patients with coronary artery disease and low HDL‐C levels are characterized by GALNT2 promoter hyper‐methylation, a proxy of gene downregulation. [ 14 ] Taken altogether these data indicate that GALNT2 increases HDL‐C and decreases triglycerides serum levels and suggest that GALNT2 downregulation is a risk factor for atherogenic dyslipidemia.…”
Section: Introductionmentioning
confidence: 89%